History and genetic diversity of African sheep: Contrasting phenotypic and genomic diversity - Da Silva, A.; Ahbara, A.; Baazaoui, I.; Jemaa, S.B.; Cao, Y.; Ciani, E.; Dzomba, E.F.; Evans, L.; Gootwine, E.; Hanotte, Olivier H.; Harris, L.; Li, M.-H.; et al. (2025)
Domesticated sheep have adapted to contrasting and extreme environments and continue to play important roles in local community-based economies throughout Africa. Here we review the Neolithic migrations of thin-tailed sheep and the later introductions of fat-tailed sheep into eastern Africa. According to contemporary pictorial evidence, the latter occurred in Egypt not before the Ptolemaic period (305–25 BCE). We further describe the more recent history of sheep in Egypt, the Maghreb, west and central Africa, central-east Africa, and southern Africa. We also present a comprehensive molecular survey based on the analysis of 50 K SNP genotypes for 59 African breeds contributed by several laboratories. We propose that gene flow and import of fat-tailed sheep have partially overwritten the diversity profile created by the initial migration. We found a genetic contrast between sheep north and south of the Sahara and a west–east contrast of thin- and fat-tailed sheep. There is no close relationship between African and central and east Asian fat-tailed breeds, whereas we observe within Africa only a modest effect of tail types on breed relationships.